CAN ACCOUNTING BE AN INTERNATIONAL LANGUAGE? - Wilkinson, Theodore L. (The Accounting Review, 1964)
Under-developed countries and many developed countries need outside capital for expansion. The residents of other countries have capital to invest, but they need accounting that they can understand, at two stages. First, to select the businesses they are going to invest in and second, to know how their investments are doing. They cannot do that today because there are different accounting rules in different countries. There are variations from one country to another not only in accounting principles but also in reporting practices, that is, what management customarily discloses to investors and prospective investors. One simple conclusion is that when the citizens of one country invest capital in enterprises in a second country, the accounting principles of the investor nation will follow the capital. Another reason for differences in accounting is found in the legal traditions of the countries. It is quite possible for two countries having similar practices to diverge during the course of their economic development and adopt different accounting customs.